Assessing the Implications of Agricultural Mechanisation for Customary Land Tenure Relations in the Transitional Zone, Ghana - Kwasi Sarfo; Bernard Okoampah Otu; Michael Atakro (Africa Spectrum)
Agricultural mechanisation promotes continuous cultivation on a piece of land and expansion of the area under cultivation, thereby intensifying competition for land. This impacts the land tenure system based on customary land tenure and communal landholding that thrived under land fallowing. Situated within the evolutionary theory of land rights and adopting an empirical qualitative research approach, this paper examines the effects of agricultural mechanisation on customary land tenure relations in Ghana's Transitional Zone. The paper argues that the widespread adoption of agricultural mechanisation has led to farm extensification and intensification which have engendered intense competition and conflicts over land and trends towards individual landholding. This has provided the arsenals for manipulation by the powerful in society and ushering in a new form of customary land tenure relations that replaces traditional social relations with capitalist relations and creates tension between allodial rights holders and the usufructuary and customary tenancy rights holders